If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 10 + -4x + -6 + -2x = 6 Reorder the terms: 10 + -6 + -4x + -2x = 6 Combine like terms: 10 + -6 = 4 4 + -4x + -2x = 6 Combine like terms: -4x + -2x = -6x 4 + -6x = 6 Solving 4 + -6x = 6 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-4' to each side of the equation. 4 + -4 + -6x = 6 + -4 Combine like terms: 4 + -4 = 0 0 + -6x = 6 + -4 -6x = 6 + -4 Combine like terms: 6 + -4 = 2 -6x = 2 Divide each side by '-6'. x = -0.3333333333 Simplifying x = -0.3333333333
| 3=y-7 | | 0.3y^2+0.4y^2-0.2y^2= | | 5.6q-5.5-5.7q=-1.1q-4.9 | | 2s-14s=84 | | 5y(2x+3)=65 | | m/8+4=16 | | 21x^2-4x-1=0 | | 12x-234=4x-10 | | 5y^2+7y^2+2=0 | | -2=3x/5+1 | | 4z+8z=z-7-5z | | 4x+2x=36 | | -9(8)-3(8)-8(6)=-7 | | 7x-(6x+8)=-3 | | 12-8x=172-43x | | 14x+(3x+10)=180 | | 5(8)+2(8)+6(6)=92 | | 9(8)+9(8)+6(6)=180 | | 2x+3x-15=20 | | 0.15x+0.05(4-x)=0.10(-6) | | -5(2x+3)+8x-9=6x-8(x+3) | | 6(z-7)=7z-4 | | 3x+7=3(x-6) | | 7u^2-6x-1=0 | | -(14-a)= | | 5(8)+8(8)-9(6)=50 | | 89-3x=7-8x | | X^3+4x^2+21x=0 | | -5(7)-9(9)+2(0)=5 | | 3r^2+270=0 | | -9(7)+8(9)+8(0)=12 | | -8(7)+2(9)+6(0)=-38 |